Sodium ion layered oxide as well as preparation method and application thereof
By doping magnesium chloride and magnesium oxide in sodium ion layered oxides and using tin oxide coating technology, combining low temperature sintering and melt sintering, the problems of poor conduction capacity and low compaction density of sodium ion layered oxides are solved. , achieving the improvement of high electron conductivity and electrochemical performance.
Patent Information
- Application Number
- CN202411380204.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
The conduction capacity of sodium ion layered oxides is poor, with many side reactions and low compaction density, making it difficult to meet the requirements of high capacity and high electrochemical performance.
By doping magnesium chloride and magnesium oxide, using tin oxide surface coating, combined with low-temperature sintering and melt sintering technology, a layered structure of sodium nickel iron-manganese hydroxide with high crystallinity and consistency is formed, improving the compressive resistance of the material and electrochemical properties.
It significantly improves the electron conductivity of sodium ion layered oxides, reduces side reactions, enhances the compaction density and structural stability of the material, thereby improving the electrochemical performance.
Smart Images

Figure CN119297231A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sodium ion batteries, and in particular to sodium ion layered oxides and preparation methods and applications thereof. Background Art
[0002] Lithium-ion batteries have been widely used in 3C products and electric vehicles due to their high energy density, long cycle life and environmental friendliness. However, lithium resources are limited and unevenly distributed. As demand increases, the cost will be too high and hinder its development. For this reason, it is necessary to find a substitute for lithium-ion batteries. The working mechanism of sodium-ion batteries is similar to that of lithium-ion batteries. Although they are slightly inferior in energy density, they still have obvious advantages over other types of batteries. At the same time, due to the abundant reserves, wide distribution and low cost of sodium, sodium-ion batteries are regarded as an ideal supplement and replacement for lithium-ion batteries, and are expected to be used in scenarios such as large-scale energy storage equipment.
[0003] The positive active materials of sodium ion batteries mainly include transition metal oxides, polyanionic compounds, Prussian blue and its derivatives, and organic compounds. Transition metal oxides can be divided into layered structures and tunnel structures. Among them, the general formula of sodium ion layered oxides can be expressed as Na x TMO2, composed of alternating layers of NaO2 and TMO2, has high theoretical specific capacity and voltage, simple preparation method, and highly controllable composition. It is one of the most promising positive electrode materials for sodium-ion batteries. However, in order to achieve high capacity, sodium-ion layered oxides adopt a polycrystalline structure, which makes the layered oxide material have poor ion conduction ability, many side reactions, and low compaction density. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a sodium ion layered oxide and a preparation method and application thereof, wherein the sodium ion layered oxide has high electron conductivity, few side reactions and high compaction density.
[0005] In a first aspect of the present application, a sodium ion layered oxide is provided, wherein the sodium ion layered oxide comprises, from inside to outside:
[0006] The core layer includes sodium nickel iron manganese hydroxide, and the general formula of sodium nickel iron manganese hydroxide is Na x Ni a Fe b Mn c O d , a+b+c=1, 0.1≤a≤0.9, 0.5≤b / c≤2, x:a=2~2.5:0.3, sodium nickel iron manganese hydroxide is doped with magnesium chloride;
[0007] a first coating layer, the first coating layer comprising magnesium oxide;
[0008] The second coating layer includes tin oxide.
[0009] The sodium ion layered oxide according to the first aspect of the present application has the following beneficial effects:
[0010] The sodium ion layered oxide is doped with magnesium and coated with oxide, and the synthesized material has high crystallinity and consistency, which effectively reduces surface side reactions and intercrystalline cracks, and improves the material's compressive strength and electrochemical properties. The surface doping and coating of tin elements makes the synthesized material more regular and has higher structural stability, which improves the material's compressive strength and structural reversibility, thereby increasing the compaction density and further reducing side reactions.
[0011] Among them, the size of d is obtained by balancing according to the valence states of Na, Ni, Fe, and Mn and the sizes of x, a, b, and c in a manner well known in the art.
[0012] In some embodiments of the present application, the ratio of I(110) / I(010) of the sodium ion layered oxide is not higher than 1.2, for example, it can be 1.15, 1.1, 1.05, 1, 0.95, 0.90, 0.85, or 0.80.
[0013] In some embodiments of the present application, the compaction density of the sodium ion layered oxide at a pressure of 5T is 3.0 to 4.0 g / cm 3 , for example, it can be 3.0 g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4.0g / cm 3 .
[0014] In some embodiments of the present application, the ionic conductivity of the sodium ion layered oxide is ≥ 0.5×10 -8 S / m, specifically 0.5×10 -8 ~1×10 -7 S / m, for example, can be 0.5×10 -8 S / m, 0.6×10 -8 S / m, 0.7×10 -8 S / m, 0.8×10-8 S / m, 0.9×10 -8 S / m, 1×10 -8 S / m, 2×10 -8 S / m, 3×10 -8 S / m, 4×10 -8 S / m, 5×10 -8 S / m, 6×10 -8 S / m, 7×10 -8 S / m, 8×10 -8 S / m, 9×10 -8 S / m, 1×10 -7 S / m.
[0015] In a second aspect of the present application, a method for preparing the aforementioned sodium ion layered oxide is provided, the preparation method comprising the following steps:
[0016] The sodium salt and nickel iron manganese hydroxide are ball-milled and mixed, and calcined once at 400-800° C. in an oxygen atmosphere to obtain a calcined product;
[0017] The calcined product and molten magnesium chloride are calcined twice at 900-1100° C., and then magnesium oxide is added and calcined three times at 1200-1600° C. After cooling, the mixture is ground in a protective atmosphere to obtain a powder material;
[0018] The powder material is mixed with tin oxide by ball milling, calcined four times at 700-1000° C. in an oxygen atmosphere, and ground in a protective atmosphere after cooling to obtain a sodium ion layered oxide.
[0019] The preparation method according to the present application has the following beneficial effects:
[0020] The preparation method firstly increases the crystal plane (010) ratio of sodium salt and nickel iron manganese hydroxide through low temperature sintering, thereby improving the material's ability to conduct ions and reducing the occurrence of side reactions; then, melt sintering and magnesium element doping are used to control the calcination temperature of magnesium chloride so that the synthesized material has high crystallinity and consistency, effectively reducing surface side reactions and intercrystalline cracks, and controlling the calcination temperature of magnesium oxide to improve the material's compressive strength and electrochemical performance; thereafter, the surface is doped and coated with tin element to make the synthesized material more regular and have higher structural stability, thereby improving the material's compressive strength and structural reversibility, thereby increasing the compaction density and further reducing side reactions.
[0021] In some embodiments of the present application, the mass ratio of the calcined product to the molten magnesium chloride is 1 to 1.5: 1, for example, 1: 1, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1, 1.5: 1. The ratio of the calcined product to the molten magnesium chloride has a certain influence on the morphology of the sintered material. Too high or too low ratio will affect the crystal structure, thereby affecting the material properties.
[0022] In some embodiments of the present application, the amount of magnesium oxide added relative to the calcined product is 0.05-0.5wt%, for example, 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt%. The calcination temperature and addition amount of magnesium oxide have a certain influence on the compressive strength and electrochemical properties of the material. When it is too high or too low, the compressive strength and electrochemical properties of the material will deteriorate.
[0023] In some embodiments of the present application, the amount of tin oxide added relative to the powder material is 0.1-1wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%. The calcination temperature and addition amount of tin oxide affect the regularity and structural stability of the material. When it is too high or too low, the regularity and structural stability of the material will decrease.
[0024] In some embodiments of the present application, the molecular formula of nickel-iron-manganese hydroxide is Ni a Fe b Mn c (OH)2, wherein a+b+c=1, 0.1≤a≤0.9, 0.5≤b / c≤2.
[0025] In some embodiments of the present application, the amount of sodium salt and nickel iron manganese hydroxide is 2 to 2.5:0.3 according to the atomic ratio of Na:Ni, for example, it can be 2:0.3, 2.1:0.3, 2.2:0.3, 2.3:0.3, 2.4:0.3, 2.5:0.3.
[0026] In some embodiments of the present application, the sodium salt includes but is not limited to inorganic sodium salts or organic sodium salts such as sodium chloride, sodium carbonate, and sodium sulfate.
[0027] In some embodiments of the present application, tin oxide includes but is not limited to at least one of SnO, SnO2, Sn3O4, etc.
[0028] In some embodiments of the present application, the time of a single calcination is 3 to 6 hours.
[0029] In some embodiments of the present application, the first calcination further includes a heat preservation at 200-400°C.
[0030] In some embodiments of the present application, the insulation time is 6 to 12 hours.
[0031] In some embodiments of the present application, the secondary calcination time is 10 to 16 hours.
[0032] In some embodiments of the present application, the secondary calcination further includes a secondary heat preservation at 600-900°C.
[0033] In some embodiments of the present application, the secondary insulation time is 6 to 12 hours.
[0034] In some embodiments of the present application, the time for the third calcination is 10 to 16 hours.
[0035] In some embodiments of the present application, the three calcinations further include three insulations at 600-900° C.
[0036] In some embodiments of the present application, the three insulation times are 6 to 12 hours.
[0037] In some embodiments of the present application, the time for the four calcinations is 8 to 16 hours.
[0038] In some embodiments of the present application, the four calcinations further include four insulations at 400-700° C.
[0039] In some embodiments of the present application, the four insulation times are 6 to 12 hours.
[0040] In some embodiments of the present application, the heating rates of the first calcination, the second calcination, the third calcination, and the fourth calcination are independently selected from 1 to 5° C. / min.
[0041] In some embodiments of the present application, the protective atmosphere includes an atmosphere of at least one gas selected from the group consisting of nitrogen, helium, neon, and argon.
[0042] In a third aspect of the present application, a sodium ion battery is provided, which includes a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes the aforementioned sodium ion layered oxide.
[0043] In some embodiments, the sodium ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator are stacked, wound or the like to obtain a battery cell and prepare a sodium ion battery.
[0044] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector.
[0045] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on the negative electrode current collector.
[0046] In some embodiments of the present application, the negative electrode active material includes at least one of a carbon material, a sulfide, an oxide, a metal element, and an alloy material.
[0047] In some embodiments, the positive electrode current collector and the negative electrode current collector are independently selected from at least one of metal materials including metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).
[0048] In some of the embodiments, the electrolyte may be at least one of a solid electrolyte or an electrolyte solution.
[0049] In a fourth aspect of the present application, an electrical device is provided, which comprises the aforementioned sodium ion battery.
[0050] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more energy forms, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc. Additional aspects and advantages of the present application will be partially given in the following description, and some will become obvious from the following description, or will be understood through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 This is a SEM image of the sodium ion layered oxide of Example 1 of the present application.
[0052] Figure 2 It is a SEM image of the sodium ion layered oxide of Comparative Example 2 of the present application.
[0053] Figure 3 It is a SEM image of the sodium ion layered oxide of Comparative Example 3 of the present application. DETAILED DESCRIPTION
[0054] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.
[0055] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.
[0056] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0057] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0058] The present application is described below in conjunction with specific embodiments.
[0059] The present application embodiment relates to a Ni 0.3 Fe 0.4 Mn 0.3 (OH)2 precursor, which can be prepared by the following coprecipitation method:
[0060] According to the molar ratio of Ni:Fe:Mn of 3:4:3, nickel sulfate, iron sulfate and manganese sulfate were prepared into a mixed solution, and 10 mol / L ammonia water and 10 mol / L NaOH solution were added to the reactor by a metering pump at the same time; the stirring speed was controlled at 350 rpm under nitrogen protection at 60°C, and the pH was adjusted to 11.5. Feeding was stopped when the precursor particles grew to 15 μm; after stirring for 30 minutes, the slurry was aged, placed in a centrifuge, washed several times with NaOH solution and hot pure water, and the precipitate was dried and sieved to obtain the precursor.
[0061] Example 1
[0062] This embodiment provides a sodium ion layered oxide, and the preparation process is as follows:
[0063] (1) Sodium chloride and Ni prepared by coprecipitation 0.3 Fe 0.4Mn 0.3 The (OH)2 precursor was weighed according to the stoichiometric ratio of Na:Ni=2.2:0.3, mixed thoroughly by ball milling, and then dried in air. The obtained sample mixture was pressed into a spherical shape, calcined at 600°C for 5 hours (heating rate of 5°C / min) in an oxygen atmosphere, and kept at 400°C for 12 hours to obtain a calcined product after keeping the temperature.
[0064] (2) The calcined product after insulation is mixed with an equal mass of molten MgCl2, calcined at 1000°C for 16 hours (heating rate of 5°C / min), and kept at 800°C for 12 hours, and then 0.25wt% of MgO in mass of the calcined product in step (1) is added, calcined at 1400°C for 16 hours (heating rate of 5°C / min), and kept at 900°C for 6 hours. After cooling, the mixture is ground in an inert atmosphere to obtain a powder material.
[0065] (3) Add 0.5 wt% SnO2 of the mass of the powder material in step (2) to the powder material obtained by grinding in step (2), mix thoroughly by ball milling, calcine at 850° C. for 16 hours (heating rate of 5° C. / min) in an oxygen atmosphere, keep warm at 500° C. for 12 hours, and grind in an inert atmosphere after cooling to obtain a sodium ion layered oxide.
[0066] Example 2
[0067] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (1) is as follows:
[0068] (1) Sodium salt and Ni prepared by coprecipitation 0.3 Fe 0.4 Mn 0.3 The (OH)2 precursor was weighed according to the stoichiometric ratio of Na:Ni=2.2:0.3, mixed thoroughly by ball milling, and then dried in air. The obtained sample mixture was pressed into a spherical shape, calcined at 400°C for 5 hours (heating rate of 5°C / min) in an oxygen atmosphere, and kept at 400°C for 12 hours to obtain a calcined product after keeping the temperature.
[0069] Example 3
[0070] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (1) is as follows:
[0071] (1) Sodium salt and Ni prepared by coprecipitation 0.3 Fe 0.4 Mn 0.3The (OH)2 precursor was weighed according to the stoichiometric ratio of Na:Ni=2.2:0.3, mixed thoroughly by ball milling, and then dried in air. The obtained sample mixture was pressed into a spherical shape, calcined at 800°C for 5 hours (heating rate of 5°C / min) in an oxygen atmosphere, and kept at 400°C for 12 hours to obtain a calcined product after keeping the temperature.
[0072] Example 4
[0073] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (2) is as follows:
[0074] (2) The calcined product after heat preservation is mixed with an equal mass of molten MgCl2, calcined at 1000°C for 16 hours (heating rate of 5°C / min), kept at 800°C for 12 hours, and then 0.05% by mass of MgO is added, calcined at 1400°C for 16 hours (heating rate of 5°C / min), kept at 900°C for 6 hours, and ground in an inert atmosphere after cooling to obtain a powder material.
[0075] Example 5
[0076] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (2) is as follows:
[0077] (2) The calcined product after heat preservation is mixed with an equal mass of molten MgCl2, calcined at 1000°C for 16 hours (heating rate of 5°C / min), kept at 800°C for 12 hours, and then 0.5% by mass of MgO is added, calcined at 1400°C for 16 hours (heating rate of 5°C / min), kept at 900°C for 6 hours, and ground in an inert atmosphere after cooling to obtain a powder material.
[0078] Example 6
[0079] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (2) is as follows:
[0080] (2) The calcined product after heat preservation is mixed with an equal mass of molten MgCl2, calcined at 900°C for 16 hours (heating rate of 5°C / min), kept at 800°C for 12 hours, and then 0.25% by mass of MgO is added, calcined at 1400°C for 16 hours (heating rate of 5°C / min), kept at 900°C for 6 hours, and ground in an inert atmosphere after cooling to obtain a powder material.
[0081] Example 7
[0082] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (2) is as follows:
[0083] (2) The calcined product after heat preservation is mixed with an equal mass of molten MgCl2, calcined at 1100°C for 16 hours (heating rate of 5°C / min), kept at 800°C for 12 hours, and then 0.25% by mass of MgO is added, calcined at 1400°C for 16 hours (heating rate of 5°C / min), kept at 900°C for 6 hours, and ground in an inert atmosphere after cooling to obtain a powder material.
[0084] Example 8
[0085] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (2) is as follows:
[0086] (2) The calcined product after heat preservation is mixed with an equal mass of molten MgCl2, calcined at 1000°C for 16 hours (heating rate of 5°C / min), kept at 800°C for 12 hours, and then 0.25% by mass of MgO is added, calcined at 1200°C for 16 hours (heating rate of 5°C / min), kept at 900°C for 6 hours, and ground in an inert atmosphere after cooling to obtain a powder material.
[0087] Example 9
[0088] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (2) is as follows:
[0089] (2) The calcined product after heat preservation is mixed with an equal mass of molten MgCl2, calcined at 1000°C for 16 hours (heating rate of 5°C / min), kept at 800°C for 12 hours, and then 0.25% by mass of MgO is added, calcined at 1600°C for 16 hours (heating rate of 5°C / min), kept at 900°C for 6 hours, and ground in an inert atmosphere after cooling to obtain a powder material.
[0090] Example 10
[0091] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (3) is as follows:
[0092] (3) Add 0.1% by mass of tin oxide to the powder material obtained by grinding in step (2), mix thoroughly by ball milling, calcine at 850° C. for 16 hours (heating rate of 5° C. / min) in an oxygen atmosphere, keep warm at 500° C. for 12 hours, and grind in an inert atmosphere after cooling to obtain a sodium ion layered oxide.
[0093] Embodiment 11
[0094] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (3) is as follows:
[0095] (3) Add 1% by mass of tin oxide to the powder material obtained by grinding in step (2), mix thoroughly by ball milling, calcine at 850° C. for 16 hours (heating rate of 5° C. / min) in an oxygen atmosphere, keep warm at 500° C. for 12 hours, and grind in an inert atmosphere after cooling to obtain a sodium ion layered oxide.
[0096] Example 12
[0097] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (3) is as follows:
[0098] (3) Add 0.5% by mass of tin oxide to the powder material obtained by grinding in step (2), mix thoroughly by ball milling, calcine at 700° C. for 16 hours (heating rate of 5° C. / min) in an oxygen atmosphere, keep warm at 500° C. for 12 hours, and grind in an inert atmosphere after cooling to obtain a sodium ion layered oxide.
[0099] Embodiment 13
[0100] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (3) is as follows:
[0101] (3) Add 0.5% by mass of tin oxide to the powder material obtained by grinding in step (2), mix thoroughly by ball milling, calcine at 1000° C. for 16 hours (heating rate of 5° C. / min) in an oxygen atmosphere, keep warm at 500° C. for 12 hours, and grind in an inert atmosphere after cooling to obtain a sodium ion layered oxide.
[0102] Embodiment 14
[0103] This embodiment provides a sodium ion layered oxide, and the preparation steps thereof are different from those of embodiment 1 in that step (1) is as follows:
[0104] (1) Sodium salt and Ni prepared by coprecipitation 0.3 Fe 0.4 Mn 0.3 The (OH)2 precursor was weighed according to the stoichiometric ratio of Na:Ni=2.2:0.3, mixed thoroughly by ball milling, and then dried in air. The obtained sample mixture was pressed into a spherical shape, calcined at 1000°C for 5 hours (heating rate of 5°C / min) in an oxygen atmosphere, and kept at 400°C for 12 hours to obtain a calcined product after keeping the temperature.
[0105] Comparative Example 1
[0106] This comparative example provides a sodium ion layered oxide, and the preparation steps thereof are different from those of Example 1 in that step (1) is specifically as follows:
[0107] (1) Sodium salt and Ni prepared by coprecipitation 0.3 Fe 0.4 Mn 0.3 The (OH)2 precursor was weighed according to the stoichiometric ratio of Na:Ni=2.2:0.3, mixed thoroughly by ball milling, and then dried in air. The obtained sample mixture was pressed into a spherical shape, calcined at 1000°C for 12 hours (heating rate of 5°C / min) in an oxygen atmosphere, and kept at 400°C for 12 hours to obtain a calcined product after keeping the temperature.
[0108] Step (1) of Example 1 promotes the growth of the crystal plane (010) by low-temperature sintering, but the conventional preparation process only uses low-temperature sintering without other supporting step parameters, which will lead to poor material properties. Therefore, this comparative example uses conventional high-temperature sintering to obtain a conventional sodium ion layered oxide material.
[0109] Comparative Example 2
[0110] This comparative example provides a sodium ion layered oxide, and its preparation steps are different from those of Example 1 in that step 2 is omitted.
[0111] Comparative Example 3
[0112] This comparative example provides a sodium ion layered oxide, and its preparation steps are different from those of Example 1 in that step 3 is omitted.
[0113] The sodium ion layered oxide materials prepared in the above Examples 1 to 14 and Comparative Examples 1 to 3 were assembled into sodium ion button cells, and the electrical performance was tested at room temperature, with a charge and discharge condition of 0.5C and a charge and discharge range of 2.0V to 4.0V. The electrical performance test results are shown in Table 1 below:
[0114] Table 1. Electrical performance test results
[0115]
[0116]
[0117] According to the test results in Table 1:
[0118] Comparing Examples 1, 2, 3, and 14 with Comparative Example 1, in Examples 1 to 3, when the low-temperature sintering reaction temperature is between 400 and 800°C, the discharge gram capacity and capacity retention rate are better than those in Comparative Example 1, and are optimal when the low-temperature sintering reaction temperature is 600°C; in Example 14, when the low-temperature sintering reaction temperature exceeds 800°C and reaches 1000°C, the discharge gram capacity and capacity retention rate are deteriorated to varying degrees, but are still better than those in Comparative Example 1. The conventional high-temperature sintering used in Comparative Example 1 is still quite different from that in the Example. If the low-temperature sintering of step (1) of Example 1 is introduced alone, the discharge gram capacity and capacity retention rate decrease more significantly than those in the Example.
[0119] Comparing Examples 1, 4, 5, 6, 7, 8, and 9 with Comparative Examples 1 to 2, in Examples 1, 4, and 5, when the mass ratio of the added MgO is 0.05% to 0.5%, the discharge gram capacity and the capacity retention rate are better than those of the comparative example, and are optimal when the mass ratio of the added MgO is 0.25%; in Examples 1, 6, and 7, when the calcination temperature of MgCl2 is 900 to 1100°C, the discharge gram capacity and the capacity retention rate are better than those of the comparative example, and are optimal when the calcination temperature of MgCl2 is 1000°C; in Examples 1, 8, and 9, when the calcination temperature of MgO is 1200 to 1600°C, the discharge gram capacity and the capacity retention rate are better than those of the comparative example, and are optimal when the calcination temperature of MgO is 1400°C; when step 2 is omitted in Comparative Example 2, the discharge gram capacity and the capacity retention rate are significantly deteriorated compared with those of Example 1.
[0120] Comparing Examples 1, 10, 11, 12, and 13 with Comparative Examples 1 and 3, in Examples 1, 10, and 11, when the mass ratio of the added tin oxide is 0.1% to 1.0%, the discharge capacity per gram and the capacity retention rate are better than those of the comparative example, and are optimal when the mass ratio of the added tin oxide is 0.5%; in Examples 1, 12, and 13, when the calcination temperature is 700 to 1000°C, the discharge capacity per gram and the capacity retention rate are better than those of the comparative example, and are optimal when the calcination temperature is 850°C; when step 3 is omitted in Comparative Example 3, the discharge capacity per gram and the capacity retention rate are significantly deteriorated compared with Example 1.
[0121] The above description shows that the low temperature sintering in step (1) and the melt sintering and magnesium doping in step (2) are beneficial to improving the electrical properties, and the method of tin surface doping and coating in step (3) can improve the electrochemical properties of the material, and when under appropriate synthesis conditions, the electrical performance effect is better than that of only melt sintering and magnesium doping and only tin surface doping and coating.
[0122] The test results of the compaction density, ion conductivity and crystal plane exposure ratio of the sodium ion layered oxides of some embodiments and comparative examples are shown in Tables 2 to 4.
[0123] Among them, the measurement method of compaction density can refer to the measurement method of powder compaction density in Appendix L of "GB / T 24533-2019 Graphite Anode Materials for Lithium-ion Batteries". Take an appropriate amount of sample and add it to the powder compaction density meter. Pressurize from 0 to 5T and maintain for 10s, then release the pressure, measure the volume of the sample, and calculate the density, which is the compaction density.
[0124] The measurement method of ionic conductivity can refer to the four-probe method in Appendix G "Measurement method of conductivity" of "GB / T 30835-2014 Carbon composite lithium iron phosphate positive electrode material for lithium ion batteries".
[0125] The crystal plane exposure ratio is calculated by obtaining the peak intensities of the (110) and (010) crystal planes from the XRD diffraction pattern, and taking the ratio of the two as the crystal plane exposure ratio.
[0126] Table 2. Compacted density test results
[0127] <![CDATA[Compaction density (5T pressure) g / cm 3 > Example 1 3.45 Example 2 3.19 Example 3 3.42 Example 4 3.25 Example 5 3.39 Example 6 3.29 Example 7 3.40 Example 8 3.27 Example 9 3.33 Example 10 3.26 Embodiment 11 3.37 Example 12 3.35 Embodiment 13 3.32 Embodiment 14 3.25 Comparative Example 1 2.78 Comparative Example 2 3.01 Comparative Example 3 3.17
[0128] Table 3. Ionic conductivity test results
[0129] <![CDATA[Ionic conductivity (10 -8 S / m)]]> Example 1 8.7 Example 2 6.5 Example 3 4.6 Embodiment 14 0.5 Comparative Example 1 0.3 Comparative Example 2 4.9 Comparative Example 3 7.2
[0130] Table 4. Crystal plane exposure ratio
[0131] I(110) / I(010) Example 1 0.92 Embodiment 14 1.15
[0132] The data in Table 2 show that the compaction densities of Examples 1 to 14 are not much different. Comparing the compaction densities of the sodium ion layered oxides of Example 1 and Comparative Examples 1 to 3, Example 1> Comparative Example 3> Comparative Example 2> Comparative Example 1, indicating that the method of melt sintering and magnesium element doping in step (2) can improve the compaction density of the material, and the improvement is greater than the method of tin element surface doping and coating in step 3. Specifically, it can be seen from Examples 1, 2, and 3 that, as the calcination temperature in step 1 increases, the compaction density first increases and then decreases slightly, indicating that by increasing the sintering temperature within a certain range, the compaction density of the material can be improved; it can be seen from Examples 1, 4, and 5 that, as the mass ratio of MgO added in step 2 increases, the compaction density first increases and then decreases, indicating that by controlling the mass ratio of MgO added within a certain range, the compaction density of the material can be improved; it can be seen from Examples 1, 6, and 7 that, as the calcination temperature of MgCl2 in step 2 increases, the compaction density first increases and then decreases slightly, indicating that by increasing the calcination temperature of MgCl2 within a certain range, the compaction density of the material can be improved; it can be seen from Examples 1, 8, and 9 that, as the calcination temperature of MgO in step 2 increases, the compaction density first increases and then decreases slightly, indicating that by increasing the calcination temperature of MgCl2 within a certain range, the compaction density of the material can be improved. The actual density increases first and then decreases, indicating that the compaction density of the material can be improved by controlling the calcination temperature of MgO within a certain range; as can be seen from Examples 1, 10, and 11, with the increase in the mass ratio of tin oxides added in step 3, the compaction density increases first and then decreases, indicating that the compaction density of the material can be improved by controlling the mass ratio of tin oxides added within a certain range; as can be seen from Examples 1, 12, and 13, with the increase in the calcination temperature in step 3, the compaction density increases first and then decreases, indicating that the compaction density of the material can be improved by controlling the calcination temperature within a certain range; in addition, as can be seen from Examples 1 and 14, the low-temperature sintering in step 1 of Example 1 forms more 010 crystal planes, which can also slightly improve the compaction density of the material.
[0133] The data in Table 3 show that the ionic conductivity of Examples 1, 2, 3 and Comparative Examples 2 and 3 is much higher than that of Example 14 and Comparative Example 1, indicating that the 010 crystal plane formed by low-temperature sintering is beneficial to improving the conductivity. Specifically, it can be seen from Examples 1, 2, and 3 that the calcination temperature in step 1 increases, and the ionic conductivity first increases and then decreases, indicating that controlling the sintering temperature within a certain range can improve the ionic conductivity of the material. In addition, the results in Table 1 also show that the sintering temperature has an effect on the electrical properties, and improving the ionic conductivity is also beneficial to the electrical properties; it can be seen from Example 1 and Comparative Example 2 that the operation of step 2 can improve the ionic conductivity. In addition, in Table 1, it can be seen that melt sintering and magnesium doping are beneficial to improving the electrical properties, and secondly, improving the ionic conductivity also has a certain effect on improving the electrical properties; it can be seen from Example 1 and Comparative Example 3 that the operation of step 3 can slightly improve the ionic conductivity. In addition, it can be seen that the surface doping and coating of tin elements is beneficial to improving the electrical properties, and secondly, improving the ionic conductivity also has a certain effect on improving the electrical properties.
[0134] The data in Table 4 show that the crystal plane I(110) / I(010) of Example 1 is lower than that of Example 14, indicating that the low temperature sintering of Example 1 forms more 010 crystal planes.
[0135] Figure 1 to Figure 3 The SEM images of the sodium ion layered oxide materials of Example 1, Comparative Example 2 and Comparative Example 3 are shown respectively. Figure 1 and Figure 2 In Example 1, the sodium ion layered oxide material has high crystallinity and consistency through melt sintering and magnesium doping in step (2); Comparison Figure 1 and Figure 3 In Example 1, the regularity of the sodium ion layered oxide material is greatly improved by surface doping and coating with tin elements.
[0136] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
Claims
1. A sodium ion layered oxide, characterized in that: Including from inside to outside: The core layer includes sodium nickel iron manganese hydroxide, and the general formula of the sodium nickel iron manganese hydroxide is Na x Ni a Fe b Mn c O d , a+b+c=1, 0.1≤a≤0.9, 0.5≤b / c≤2, x:a=2~2.5:0.3, the sodium nickel iron manganese hydroxide is doped with magnesium chloride; a first coating layer, the first coating layer comprising magnesium oxide; A second coating layer, wherein the second coating layer includes tin oxide.
2. The sodium ion layered oxide according to claim 1, characterized in that The ratio of I(110) / I(010) of the sodium ion layered oxide is not higher than 1.
2.
3. The sodium ion layered oxide according to claim 1, characterized in that The compaction density of the sodium ion layered oxide at a pressure of 5T is 3.0 to 4.0 g / cm 3 .
4. The sodium ion layered oxide according to claim 1, characterized in that The ionic conductivity of the sodium ion layered oxide is ≥ 0.5×10 -8 S / m.
5. A method for preparing a sodium ion layered oxide, characterized in that: The following steps are involved: The sodium salt and nickel iron manganese hydroxide are ball-milled and mixed, and calcined once at 400-800° C. in an oxygen atmosphere to obtain a calcined product; The calcined product and molten magnesium chloride are calcined twice at 900-1100° C., and then magnesium oxide is added and calcined three times at 1200-1600° C., and after cooling, the mixture is ground in a protective atmosphere to obtain a powder material; The powder material is mixed with tin oxide by ball milling, calcined four times in an oxygen atmosphere at 700-1000° C., and ground in a protective atmosphere after cooling to obtain the sodium ion layered oxide.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the calcined product to the molten magnesium chloride is 1-1.5:1; and / or, the amount of magnesium oxide added relative to the calcined product is 0.05-0.5wt%; and / or, the amount of tin oxide added relative to the powder material is 0.1-1wt%.
7. The preparation method according to claim 5, characterized in that: The time of the first calcination is 3 to 6 hours; and / or, the time of the second calcination is 10 to 16 hours; and / or, the time of the third calcination is 10 to 16 hours; and / or, the time of the fourth calcination is 8 to 16 hours.
8. The preparation method according to claim 5, characterized in that: The first calcination further includes a first heat preservation at 200-400°C; and / or, the second calcination further includes a second heat preservation at 600-900°C; and / or, the third calcination further includes a third heat preservation at 600-900°C; and / or, the fourth calcination further includes four heat preservations at 400-700°C.
9. A sodium ion battery, characterized in that The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material layer, and the positive electrode active material layer comprises the sodium ion layered oxide according to any one of claims 1 to 4.
10. Electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.